Pengaruh aromaterapi inhalasi lemon terhadap penurunan nyeri persalinan kala I fase aktif - Siti Cholifah; Abkar Raden; Ismarwati Ismarwati (Universitas Aisyiyah Yogyakarta, 2016)
This research to describe the effects of lemon aromatherapy inhalation on the reduction of first stage labor pain in the active phase. The study was a quasi-experimental with pre-test-post-test non equivalent control group design. Mann-Whitney bivariable analysis and linear regression for multivariable analysis. The result of this study was average of labor pain in aromatherapy group was 4.74 + 1.327 wich is lower than control group 5.79 + 1.316. Result of Mann-Whitney test is P 0.001 0.05. External variables which influence the labor pain was anxiety with the value of P 0.05. There is inhaled lemon aromatherapy effect on reducing first stage labor pain in active phase.